1995
DOI: 10.1159/000282726
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Upper Urinary Tract Calculi Treated with Extracorporeal Shock Wave Lithotripsy: Association with Bacteriuria before Treatment

Abstract: To study the characteristics of upper urinary tract calculi associated with bacteriuria, we determined the relationships between the frequency of bacteriuria and some clinical factors such as location and size of calculi. Nine hundred and fifty-eight patients, 596 with renal calculi and 362 with ureteral calculi, were subjects in the present study. Bacteriuria was found in 75 patients, 57 with renal calculi (10%) and 18 with ureteral calculi (5%). The frequency of bacteriuria was significantly higher in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…Szigeti et al found infected stones in 10% of their 57 patients with renal stones and they noted that bacteriuria was more prevalent in stones greater than 30mm in diameter. 20 Although in our series stone bulk did not directly correlate with uro sepsis, more of the larger stones(greater than 20mm ) were infected. We also noted that the turbidity of urine at pelvicaliceal system puncture did not correlate with SIRS and positive Pelvic urine because only 50% of the patients with cloudy urine had infected stones or positive pelvic urine culture.…”
Section: Discussion:-contrasting
confidence: 66%
“…Szigeti et al found infected stones in 10% of their 57 patients with renal stones and they noted that bacteriuria was more prevalent in stones greater than 30mm in diameter. 20 Although in our series stone bulk did not directly correlate with uro sepsis, more of the larger stones(greater than 20mm ) were infected. We also noted that the turbidity of urine at pelvicaliceal system puncture did not correlate with SIRS and positive Pelvic urine because only 50% of the patients with cloudy urine had infected stones or positive pelvic urine culture.…”
Section: Discussion:-contrasting
confidence: 66%
“…They diagnosed 10% of the patients with an infected stone and found out that in cases of a stone size bigger than 30 mm, bacteruria is more common [20]. In our study stone burden is related with SIRS or with urosepsis in the ciprofloxacin group but there is no such relationship with the ceftriaxone group.…”
Section: Commentmentioning
confidence: 41%
“…Conversely, stone and pelvic urine C&S were better predictors of urosepsis after surgery and large stones appeared more likely to be infected. Shigeta et al [12] found infected stones in 10% of their 57 patients with renal stones, and found that bacteriuria was more prevalent in stones of > 30 mm in diameter. However, Gault et al [13] attributed the lower risk of infected stones in their series (5.6%) to a longer period of preoperative antibiotics, using fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%